Safety and Efficacy of a tCD25 Preselective Combination Anti-HIV Lentiviral Vector in Human Hematopoietic Stem and Progenitor Cells. (17th February 2015) - Barclay, Sharlie L.; Yang, Yimin; Zhang, Siruo; Fong, Ryan; Barraza, Alfonso; Nolta, Jan A.; Torbett, Bruce E.; Abedi, Mehrdad; Bauer, Gerhard; Anderson, Joseph S.
Abstract: The successful suppression of human immunodeficiency virus (HIV) in the "Berlin Patient" has highlighted the ability of HIV-resistant hematopoietic stem cells to offer a potential functional cure for HIV-infected patients. HIV stem cell gene therapy can mimic this result by genetically modifying a patient's own cells with anti-HIV genes. Previous attempts of HIV gene therapy have been hampered by a low percentage of transplanted HIV-resistant cells which has led to minimal clinical efficacy. In our current study, we have evaluated the in vitro and in vivo safety and efficacy of a truncated/mutated form of human CD25 preselective anti-HIV lentiviral vector in human hematopoietic stem cells. This preselective vector allows us to purify vector-transduced cells prior to transplantation so an increased percentage of gene-modified cells can be delivered. Here, we demonstrate the safety of this strategy with successful engraftment and multilineage hematopoiesis of transduced cells in a humanized NOD-RAG1−/−IL-2rγ−/− knockout mouse model. Efficacy was also demonstrated with significant protection from HIV-1 infection including maintenance of human CD4+ cell levels and a decrease in HIV-1 plasma viremia. Collectively, these results establish the utility of this HIV stem cell gene therapy strategy and bring it closer to providing a functional cure for HIV-infected patients. Stem Cells 2015;33:870–879